2021
DOI: 10.3390/polym13213683
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Silver Nanoparticles as an Effective Antibiofouling Material for Polyvinylidene Fluoride (PVDF) Ultrafiltration Membrane

Abstract: Silver nanoparticles (AgNPs) were successfully synthesized using the aqueous extract of the Paronychia argentea Lam (P. argentea) wild plant. The results showed that the conversion of Ag+ to Ag0 nanoparticles ratio reached 96.5% as determined by Inductively Coupled Plasma Atomic Emission Spectroscopy (ICP-AES), with a negative zeta potential (ζ) of −21.3 ± 7.68 mV of AgNPs expected to improve the stability of synthesized AgNPs. AgNP antibacterial activity has been examined against Streptococcus aureus (S. aure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 82 publications
1
10
0
Order By: Relevance
“…Meanwhile, the obtained membrane had an outstanding antifouling property due to the high hydrophilicity of the modified membrane. Currently, an increasing number of nanomaterials have been attempted to be blended into PVDF matrix, such as metal nanoparticles (Alnairat et al, 2021), covalent organic frameworks (COFs) (Xu et al, 2020;Qian et al, 2022), carbon nanotubes (CNTs) (Ayyaru et al, 2019;Gholami et al, 2022) etc. Thus, the choose and control of nanoparticles in UF membrane is crucial important.…”
mentioning
confidence: 99%
“…Meanwhile, the obtained membrane had an outstanding antifouling property due to the high hydrophilicity of the modified membrane. Currently, an increasing number of nanomaterials have been attempted to be blended into PVDF matrix, such as metal nanoparticles (Alnairat et al, 2021), covalent organic frameworks (COFs) (Xu et al, 2020;Qian et al, 2022), carbon nanotubes (CNTs) (Ayyaru et al, 2019;Gholami et al, 2022) etc. Thus, the choose and control of nanoparticles in UF membrane is crucial important.…”
mentioning
confidence: 99%
“…These nanoparticles exhibited impressive antifouling performance against bacterial strains like Streptococcus aureus (S. aureus) and Escherichia coli (E. coli), as documented by Alnairat and co-workers. 46 Another study also reported the incorporation of AgNPs into polyamide 12 membranes that were obtained by the selective laser sintering method that was followed by washing, pretreatment, and functionalization with alkoxides and silanes. 47 More studies that report the use of AgNPs in polymeric membranes include the incorporation into poly(ether sulfone) membranes to develop antibacterial and antifouling ultrafiltration membranes 48 and into polysulfone ultrafiltration membranes among others.…”
Section: Nanoparticle-based Polymericmentioning
confidence: 99%
“…Hence, it is highly desired to explore more investigations focused on the blending materials to enhance the properties of PVDF membrane. 37,38 The amphiphilic copolymers have both hydrophobic and hydrophilic chains, while the hydrophobic segments form easily the entanglement with PVDF, are helpful to improve the dispersion and compatibility of the additives in membranes solutions. The hydrophilic segments can make the hydrophilic group segregation on the membrane surface to bind with water molecules and form hydrated layers which resist the adsorption of foulants.…”
Section: Introductionmentioning
confidence: 99%
“…It is revealed that the better dispersion and compatibility between inorganic and polymers can avoid the formation of defective interfaces in modified membranes, but the aggregation of nanoparticles would have a negative effect on permeability and antifouling performance. Hence, it is highly desired to explore more investigations focused on the blending materials to enhance the properties of PVDF membrane 37,38 …”
Section: Introductionmentioning
confidence: 99%